2001
DOI: 10.1093/ndt/16.suppl_1.70
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hypertension in renal disease

Abstract: There is a high prevalence of HTN in renal patients, which depends on the type of nephropathy and the degree of renal failure. Other independent risk factors for HTN in patients with renal disease are: advanced age, the presence of diabetes, hypertriglyceridaemia and the severity of proteinuria. BP control in renal patients is quite poor and should be improved to reduce progression of the renal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
34
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(42 citation statements)
references
References 0 publications
5
34
0
3
Order By: Relevance
“…18 It has been shown in many studies that increased volume overload is basically in an extracellular fluid compartment, which results in hypertension. 19,20 Our study by using the BIA determinations OH/ECW revealed the association between volume overload and hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…18 It has been shown in many studies that increased volume overload is basically in an extracellular fluid compartment, which results in hypertension. 19,20 Our study by using the BIA determinations OH/ECW revealed the association between volume overload and hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…13 The prevalence of hypertension increases with worsening renal function. An inverse relationship between renal functional impairment and prevalence of hypertension has been reported in the Chronic Renal Insufficiency Cohort (CRIC) study.…”
mentioning
confidence: 99%
“…The prevalence of HTN in patients with renal insufficiency was significantly higher than that in patients without renal insufficiency, which depended on the type of nephropathy and the degree of renal failure (Ridao et al, 2001). The activation of the renin-angiotensin system (RAS) is an important factor contributing to the pathogenesis of hypertension in KD by stimulating the sympathetic nervous system gjhs.ccsenet.org…”
Section: Discussionmentioning
confidence: 99%